2014
DOI: 10.1021/ef500259z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Operational Strategies for Biodiesel Production by Direct Transesterification of Microalgal Biomass

Abstract: In this study, different operational strategies for biodiesel production by direct transesterification of microalgal biomass (Botryococcus braunii) were evaluated. These operational strategies include the use of different acyl acceptors and the application of different catalysts and solvent mixtures. All these strategies were performed in two reaction systems: a conventional batch reactor (CBR) and a reflux extraction reactor (RER). The highest biodiesel production yields (80.6 wt %) were obtained in the RER u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…The optimal reaction time to achieve a high lipid conversion depends on the operating conditions and the catalyst type and varies from one minute [99] to two days [100]. Due to the incomplete lipid extraction from the B. braunii biomass (high contents of residual biomass rich in lipids), improvements to existing methods are directed towards the integrated concept of simultaneous extraction and trans/esterification, also known as direct trans/esterification or in-situ trans/esterification (ISTE) [89,101]. ISTE in batch and reflux extraction reactors in semi-continuous laboratory scales are performed under solvent/cosolvent/catalyst [89,101] conditions.…”
Section: Trans/esterificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal reaction time to achieve a high lipid conversion depends on the operating conditions and the catalyst type and varies from one minute [99] to two days [100]. Due to the incomplete lipid extraction from the B. braunii biomass (high contents of residual biomass rich in lipids), improvements to existing methods are directed towards the integrated concept of simultaneous extraction and trans/esterification, also known as direct trans/esterification or in-situ trans/esterification (ISTE) [89,101]. ISTE in batch and reflux extraction reactors in semi-continuous laboratory scales are performed under solvent/cosolvent/catalyst [89,101] conditions.…”
Section: Trans/esterificationmentioning
confidence: 99%
“…Due to the incomplete lipid extraction from the B. braunii biomass (high contents of residual biomass rich in lipids), improvements to existing methods are directed towards the integrated concept of simultaneous extraction and trans/esterification, also known as direct trans/esterification or in-situ trans/esterification (ISTE) [89,101]. ISTE in batch and reflux extraction reactors in semi-continuous laboratory scales are performed under solvent/cosolvent/catalyst [89,101] conditions. The highest FAME yield of 480% is obtained in a reflux extraction reactor using the homogenous H 2 SO 4 catalyst and a low solvent/cosolvent ratio (3:1 methanol/chloroform).…”
Section: Trans/esterificationmentioning
confidence: 99%
“…21,28,29 Several studies have shown that simultaneous extraction and transesterication in different chambers in one system could produce biodiesel directly from biomass with a high yield. [30][31][32] Continuous contact of fresh solvent with biomass facilitates the lipid transfer which is further converted to biodiesel with a catalyst. In addition, Liu et al 25 successfully impregnated the dry SCG biomass with H 2 SO 4 and the simultaneous extraction-transesterication reaction was processed in the extraction chamber with methanol.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of lipids extraction from algae is the limiting step of this process. Therefore, innovative methods are developed such are pressurized fluid extraction method (100) or in-situ transesterification of biomass into biodiesel (101,102). The pressurized fluid extraction method was successfully used for polyunsaturated fatty acids (PUFAs) extraction from Nannochloropsis oculata where the maximum fatty acid yield of 16.7…”
mentioning
confidence: 99%
“…Furthermore, addition of co-solvent also causes the increase of saturated and monounsaturated methyl esters content and improves its stability (101,102).…”
mentioning
confidence: 99%